Multiphase wet sand electrolyte, preparation method and application of multiphase wet sand electrolyte in high-temperature aqueous zinc ion battery
By using multi -phase wet sand electrolytes in zinc ion batteries, combined with organic solvents and inorganic nano particles, the problem of zinc negative side reaction and zinc branched crystal growth under high temperature, and realized the stability and life of the battery's high temperature cycle stability and life span. promote.
Patent Information
- Application Number
- CN202411421118.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Under high temperature conditions, the zinc negative electrode side of the zinc ion battery faces serious side reactions and zinc dendrites growth problems, resulting in rapid failure of the battery.
Multiphase wet sand electrolyte is used, and organic solvents and inorganic nanoparticles are added to the electrolyte to destroy the hydrogen bond network of water, inhibit the activity of free water, and form a dynamic interface layer, which synergistically reduces water activity and side reactions.
It significantly improves the cycle stability and life of zinc-ion batteries at high temperatures, reduces the generation of by-products, and improves the high-temperature performance and safety of the battery.
Smart Images

Figure CN119361862A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrolyte preparation, in particular to a multiphase wet sand electrolyte containing an organic solvent, water and inorganic nanoparticles and application of the electrolyte in a high-temperature aqueous zinc ion battery. Background Art
[0002] With the growth of energy demand and the emphasis on environmental protection, lithium-ion batteries are widely used in portable electronic devices and electric vehicles due to their high energy density and long cycle life. However, the limited resources and high cost of lithium restrict its large-scale application. Therefore, it is of great significance to develop an alternative battery system that is cost-effective, environmentally friendly and sustainable. As a potential alternative energy storage system, zinc-ion batteries have obvious advantages over lithium-ion batteries, including abundant reserves and low cost; safe and non-flammable electrolytes; a wider operating temperature range and good resistance to overcharge and over-discharge. In order to meet the special application requirements under some high temperature conditions, such as oil drilling, geothermal power generation, aerospace, etc., it is necessary to improve the performance of batteries at high temperatures, increase safety, extend battery life, and environmental adaptability to adapt to the normal operation of equipment under extreme climate conditions. However, at high temperatures, the zinc negative electrode side faces serious side reactions (including hydrogen evolution reaction (HER) and zinc corrosion) and accelerates the growth of zinc dendrites, resulting in rapid battery failure. At present, the modification strategies adopted include the use of polymer electrolytes and co-solvent electrolytes to inhibit these adverse reactions and enable the aqueous solution to circulate stably at relatively high temperatures. However, in order to meet the requirements of applications under more stringent conditions, it is necessary to discover the possibility of cycling aqueous zinc-ion batteries at higher temperatures, even reaching the boiling point of water. Therefore, in recent years, the research and development of various new electrolyte preparation processes for zinc-ion batteries has received extensive attention. Summary of the invention
[0003] The use of multiphase wet sand electrolyte to improve the high temperature cycle performance of zinc ion batteries mainly utilizes organic solvents and inorganic nanoparticles to destroy the hydrogen bond network of water, inhibit the activity of free water, improve the thermal stability of the electrolyte, and add inorganic nanoparticles to form a dynamic interface layer. The synergistic effect of the two can greatly reduce water activity and reduce side reactions. In this process, the type and content of organic solvents and inorganic nanoparticles are crucial to the final cycle performance effect. Therefore, the present application discloses a multiphase wet sand electrolyte, a preparation method and its application in high temperature aqueous zinc ion batteries: using ethylene glycol (EG), diethylene glycol (DEG), triethylene glycol (TEG), propylene glycol (PG), butanediol (BDO), n-butanol (n-Butanol), octanol (1-Octanol), pentanol (Pentanol), hexanol (1-Hexanol), isopropyl alcohol (IPA), isopentanol (Isoamyl alcohol), 2-butyl alcohol (2-butyl One or more organic solvents selected from dimethyl sulfoxide (DMSO), trimethyl phosphate (TMP), triethyl phosphate (TEP), N,N-dimethylformamide (DMF), hexamethylphosphoramide (HMPA), and pyridine (Py) are used as co-solvents. Organic co-solvents with high boiling points and strong hydrogen bonds can well destroy the hydrogen bond network of water, reduce water activity, increase the boiling point of the electrolyte, and improve the solvation structure of the zinc ion battery electrolyte. The inorganic nanoparticles forming the wet sand electrolyte include one or more of aluminum oxide (Al2O3), magnesium oxide (MgO), zinc oxide (ZnO), ferrous oxide (Fe3O4), titanium dioxide (TiO2), silicon dioxide (SiO2), strontium titanate (SrTiO3), copper oxide (CuO), calcium oxide (CaO), silicon carbide (SiC), silicon nitride (Si3N4), boron nitride (BN), hydrotalcite, montmorillonite, carbon nitride (C3N4), and zirconium phosphate (ZrP). The large inorganic nanoparticles suspended in the electrolyte can promote uniform zinc deposition, inhibit the growth of zinc dendrites, and reduce the generation of byproducts at high temperatures through the spatially ordered network structure formed by van der Waals forces or intermolecular hydrogen bonds. This new type of wet sand electrolyte has broad application prospects in the zinc ion battery electrolyte industry.
[0004] The purpose of the present invention is achieved through the following technical solutions:
[0005] A method for preparing a multiphase wet sand electrolyte comprises: dissolving a zinc salt in a mixture of water and an organic co-solvent, then adding inorganic nanoparticles, breaking the wall by ultrasound until the particles are completely dispersed and uniform, and obtaining an aqueous zinc ion multiphase wet sand electrolyte.
[0006] Furthermore, the organic co-solvent is at least one of the following compounds: ethanol (Ethanol), ethylene glycol (EG), diethylene glycol (DEG), triethylene glycol (TEG), propylene glycol (PG), propanol (Propanol), butanediol (BDO), glycerol (Glycerol), n-butanol (n-Butanol), octanol (1-Octanol), pentanol (Pentanol), hexanol (1-Hexanol), heptanol (1-Heptanol), isopropyl alcohol (IPA), isopentanol (Isoamyl alcohol) The organic co-solvent may be selected from the group consisting of 1,2-dimethylol, 2-butylalcohol, 1,2-propylene glycol (PG), 1,3-propylene glycol (1,3-PDO), 1,3-butylene glycol (1,3-Butanediol), cyclohexanol, dimethyl sulfoxide (DMSO), trimethyl phosphate (TMP), triethyl phosphate (TEP), N,N-dimethylformamide (DMF), hexamethylphosphoramide (HMPA), pyridine (Py), acetone (Acetone), tetrahydrofuran (THF), 1,4-dioxane, n-Butyl sulfone, dimethylacetamide (DMA), ethylamine, diethylamine, bis(2-methoxy ethyl)ether, acetic acid (Ac), triethanolamine, and dimethyl ether (DME). Preferably, the molar ratio of the organic co-solvent to water is 0.1 to 10.
[0007] Furthermore, the zinc salts include zinc trifluoromethanesulfonate (Zn(OTf)2), zinc sulfate (ZnSO4), zinc perchlorate (Zn(ClO4)2), zinc chloride (ZnCl2), zinc tetrafluoroborate (ZnBF4), zinc nitrate (Zn(NO3)2), zinc acetate ((CH3COO)2Zn), zinc citrate (C 12 H 14 O 16 Zn3), zinc methanesulfonate, zinc bromide (ZnBr2), zinc lactate (C6HO6Zn), zinc docosanoate, zinc undecylenate (CHO4Zn), zinc bromate (Zn(BrO3)2), zinc citrate (C 12 H 14 O 16 Zn3), zinc diethyldithiocarbamate (DBZ), zinc salicylate (C 14 H 10 O6Zn), zinc stearate (C 36 H 70 O4Zn), Zinc p-toluenesulfonate (C 14 H14 O6S2Zn), benzenesulfinate zinc (C 12 H 14 O6S2Zn), zinc trifluoroacetate (C2F3O2Zn), zinc sulfamate (H3NO3SZn), zinc formate (C2H2O4Zn), zinc oxalate (ZnC2O4.2H2O) or a mixture of two or more thereof. Preferably, the concentration of the zinc salt in the electrolyte is 0.5M-5M.
[0008] Further, the inorganic nanoparticles are one or a mixture of two or more of aluminum oxide (Al2O3), magnesium oxide (MgO), zinc oxide (ZnO), ferrous oxide (Fe3O4), titanium dioxide (TiO2), silicon dioxide (SiO2), strontium titanate (SrTiO3), copper oxide (CuO), calcium oxide (CaO), silicon carbide (SiC), silicon nitride (Si3N4), boron nitride (BN), hydrotalcite, montmorillonite, carbon nitride (C3N4), and zirconium phosphate (ZrP). Preferably, the inorganic nanoparticles account for 1 to 50% of the total mass of the electrolyte.
[0009] Furthermore, the size of the inorganic nanoparticles ranges from 5 to 100 nanometers.
[0010] The above-mentioned method for preparing the zinc ion battery electrolyte, the raw materials involved are all commercially available, and the equipment and processes used are well known to those skilled in the art. It can be well applied in high-temperature aqueous zinc ion batteries.
[0011] The advantages and positive effects of the present invention are:
[0012] 1. The method of the present invention has low cost, simple operation and safe drug ingredients.
[0013] 2. The present invention introduces alcohol organic solvents as co-solvents in zinc ion batteries, which can reshape the hydrogen bond network, reduce water activity, and adjust the solvation structure. The oxide particles are added to the electrolyte to adjust the SEI composition. The synergistic effect of the two can reduce water activity, reduce the generation of by-products, and improve gas production, so that the zinc ion battery can have a longer life and better performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 The time-voltage curves of the symmetrical battery of Example 1 and the comparative sample at high temperature;
[0015] Figure 2 The charge and discharge curves of the full battery of Example 1 and the comparison sample at high temperature;
[0016] Figure 3 The time-voltage curves of the symmetrical battery of Example 2 and the comparative sample at high temperature;
[0017] Figure 4 The charge and discharge curves of the full battery of Example 2 and the comparison sample at high temperature. DETAILED DESCRIPTION
[0018] The following is further described in conjunction with specific examples. It should be understood that these examples are used to illustrate the present invention but not to limit the scope of the present invention. The implementation conditions used in the examples can be further adjusted according to specific construction conditions, and the implementation conditions not specified are usually the conditions in conventional experiments.
[0019] Example 1
[0020] A method for preparing a zinc ion battery electrolyte comprises: dissolving 3.05 mg Zn(OTf)2 in a mixed solution of 4 mL EG and 0.2 mL H2O, and ultrasonicating until the Zn(OTf)2 is completely dissolved. Adding 30% TiO2 (with a size range of about 20 nm) of the total electrolyte mass, and breaking the wall with a wall breaking machine until the TiO2 is completely dispersed in the electrolyte to obtain a zinc ion battery wet sand electrolyte.
[0021] Preparation method of comparative sample: 1.45 mg Zn(OTf)2 was dissolved in 2 mL H2O, and ultrasonic was applied until Zn(OTf)2 was completely dissolved to obtain zinc ion battery electrolyte.
[0022] The prepared zinc-ion battery multiphase wet sand electrolyte was used to assemble a zinc-zinc symmetric battery. The time-voltage curve of the long cycle test at high temperature is shown in Figure 1 As shown, at 80°C, the current density is 1 mA / cm 2 , capacity is 0.5 mAh / cm 2 , and can maintain a stable cycle of 1115h and a polarization voltage of 0.15V, which can illustrate the stability of the electrolyte at high temperature. It can be inferred that the interface problems and the activity of water are significantly suppressed, and the cycle life is improved.
[0023] Positive electrode material preparation method: polyaniline, conductive carbon, and PVDF are mixed into a slurry in a mass ratio of 8:1:1, coated on a carbon cloth, and dried in a vacuum drying oven at 80°C for 12 hours to obtain a positive electrode sheet.
[0024] The whole battery assembly method is as follows: using polyaniline with a diameter of 10 mm as the positive electrode sheet, a zinc sheet with a diameter of 12 mm as the negative electrode sheet, and glass fiber GF-F as the separator, dripping the above-mentioned wet sand electrolyte, and encapsulating under a pressure of 1.0 T.
[0025] The full-battery zinc-ion battery prepared has a full-battery cycle stability test curve tested at high temperature as shown in the following figure: Figure 2As shown, at 80°C and a current density of 1 A / g, the capacity retention rate can reach 70% at 1736 cycles. At the same time, it exhibits a high discharge specific capacity of 127 mAh / g at high temperature, which indicates that the electrolyte still maintains good high-temperature cycle stability in the full battery. It can be inferred that the solvation structure is optimized, the side reactions are significantly suppressed, and the cycle life is improved.
[0026] Example 2
[0027] A method for preparing a zinc ion battery electrolyte comprises: dissolving 1.59 mg Zn(OTf)2 in a mixed solution of 2 mL DEG and 0.188 mL H2O, and ultrasonicating until the Zn(OTf)2 is completely dissolved. Adding 10% Al2O3 (size range is about 20 nm) of the total electrolyte mass, and breaking the wall with a wall breaking machine until the Al2O3 is completely dispersed in the electrolyte to obtain a zinc ion battery multiphase wet sand electrolyte.
[0028] Preparation method of comparative sample: 1.59 mg Zn(OTf)2 was dissolved in a mixed solution of 2 mL DEG and 0.188 mL H2O, and ultrasonic treatment was performed until Zn(OTf)2 was completely dissolved to obtain a zinc ion battery electrolyte.
[0029] The prepared zinc-ion battery multiphase wet sand electrolyte was used to assemble a zinc-zinc symmetric battery. The time-voltage curves of the battery tested at high temperature and different current densities are shown in Figure 2. Figure 3 As shown, at 80°C, the current density increases from 0.5 to 8 mA / cm 2 When the electrolyte is charged, the minimum polarization voltage can be maintained, which indicates that the electrolyte can maintain cycle stability under high temperature and large current. It can be inferred that the interface problem and the activity of water are significantly suppressed, and the cycle life is improved.
[0030] Positive electrode material preparation method: polyaniline, conductive carbon, and PVDF are mixed into a slurry in a mass ratio of 8:1:1, coated on a carbon cloth, and dried in a vacuum drying oven at 80°C for 12 hours to obtain a positive electrode sheet.
[0031] The whole battery assembly method is as follows: using polyaniline with a diameter of 10 mm as the positive electrode sheet, a zinc sheet with a diameter of 12 mm as the negative electrode sheet, and glass fiber GF-F as the separator, dripping the above-mentioned wet sand electrolyte, and encapsulating under a pressure of 1.0 T.
[0032] The full-battery zinc-ion battery prepared has a full-battery cycle stability test curve tested at high temperature as shown in the following figure: Figure 4As shown, at 80°C and a current density of 1 A / g, the capacity retention rate can reach 48% at 1700 cycles. At the same time, it exhibits a high discharge specific capacity of 120 mAh / g at high temperature, which indicates that the electrolyte still maintains good high-temperature cycle stability in the full battery. It can be inferred that the solvation structure is optimized, the side reactions are significantly suppressed, and the cycle life is improved.
[0033] The above contents are further detailed descriptions of the invention in combination with specific embodiments, and it cannot be determined that the specific implementation of the invention is limited to these descriptions. For those skilled in the art of the present invention, any obvious simple deduction or replacement without departing from the concept of the present invention is within the scope of protection of the present invention.
Claims
1. A method for preparing a multiphase wet sand electrolyte, characterized in that: The preparation method comprises the following steps: dissolving zinc salt into a mixture of water and an organic co-solvent, then adding inorganic nanoparticles, breaking the wall by ultrasonication until the particles are completely dispersed and uniformly dispersed, and obtaining an aqueous zinc ion multiphase wet sand electrolyte.
2. The method for preparing a multiphase green sand electrolyte according to claim 1, characterized in that: The organic co-solvent is at least one of the following compounds: ethanol, ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, propanol, butanediol, glycerol, n-butanol, octanol, pentanol, hexanol, heptanol, isopropanol, isopentanol, 2-butanol, 1,2-propylene glycol, 1,3-propylene glycol, 1,3-butanediol, cyclohexanol, dimethyl sulfoxide, trimethyl phosphate, triethyl phosphate, N,N-dimethylformamide, hexamethylphosphoramide, pyridine, acetone, tetrahydrofuran, dioxane, butane sulfone, dimethylacetamide, ethylamine, diethylamine, dimethanol diethyl ether, acetic acid, triethanolamine, and dimethyl ether.
3. The method for preparing a multiphase green sand electrolyte according to claim 1, characterized in that: The molar ratio of the organic co-solvent to water is 0.1-10.
4. The method for preparing a multiphase green sand electrolyte according to claim 1, characterized in that: The zinc salt is one or a mixture of two or more of zinc trifluoromethanesulfonate, zinc sulfate, zinc perchlorate, zinc chloride, zinc tetrafluoroborate, zinc nitrate, zinc acetate, zinc citrate, zinc methanesulfonate, zinc bromide, zinc lactate, zinc behenate, zinc undecylenate, zinc bromate, zinc citrate, zinc diethyldithiocarbamate, zinc salicylate, zinc stearate, zinc p-toluenesulfonate, zinc benzenesulfinate, zinc trifluoroacetate, zinc sulfamate, zinc formate, and zinc oxalate.
5. The method for preparing a multiphase green sand electrolyte according to claim 1, characterized in that: The concentration of the zinc salt in the electrolyte is 0.5M-5M.
6. The method for preparing a multiphase green sand electrolyte according to claim 1, characterized in that: The inorganic nanoparticles are one or a mixture of two or more of aluminum oxide, magnesium oxide, zinc oxide, ferroferric oxide, titanium dioxide, silicon dioxide, strontium titanate, copper oxide, calcium oxide, silicon carbide, silicon nitride, boron nitride, hydrotalcite, montmorillonite, carbon nitride, and zirconium phosphate.
7. The method for preparing a multiphase green sand electrolyte according to claim 1, characterized in that: The inorganic nanoparticles account for 1 to 50% of the total mass of the electrolyte.
8. The method for preparing a multiphase green sand electrolyte according to claim 1, characterized in that: The size of the inorganic nanoparticles ranges from 5 to 100 nanometers.
9. A multiphase wet sand electrolyte prepared by the method for preparing a multiphase wet sand electrolyte according to any one of claims 1 to 9.
10. Use of a multiphase wet sand electrolyte prepared by the method for preparing a multiphase wet sand electrolyte according to any one of claims 1 to 9, characterized in that: Used in high-temperature aqueous zinc-ion batteries.
Citation Information
Patent Citations
Electrolyte containing inorganic additive and lithium-ion battery containing electrolyte
CN105938919A
Aqueous mixed electrolyte and application thereof in zinc ion hybrid supercapacitor
CN112927949A
Wet sand electrolyte for aqueous zinc ion battery, preparation method of wet sand electrolyte and aqueous zinc ion battery
CN114976299A
Organic-inorganic hybrid microsphere and application thereof as electrolyte additive in zinc ion battery
CN116780000A
Water system deep eutectic electrolyte and preparation method and application thereof
CN117913384A